Parental Barriers and Sociodemographic Disparities in Childhood Vaccination Post-COVID-19 in Tennessee - Sanjaya Regmi; Elizabeth Sowell; Chenoa D. Allen; Benjamin E. Jones; Nan M. Gaylord; Victoria Niederhauser (Vaccines)
Introduction: The COVID-19 pandemic disrupted routine childhood vaccinations schedules, posing significant challenges among underserved communities. Understanding how different sociodemographic groups in Tennessee perceive and navigate childhood vaccination barriers is critical for developing strategies to improve vaccination rates and reduce vulnerability to vaccine-preventable diseases. Methods: A cross-sectional survey was conducted to explore barriers to vaccination across diverse sociodemographic groups in Tennessee. Data were collected from caregivers/parents of children aged 18 years and younger across all 95 counties in Tennessee at community events and through partnerships with schools and other local organizations. Parental responses were analyzed to identify barriers in access, concern, and importance domains. The distribution of barriers across different sociodemographic groups such as race, income, education level, and insurance status was identified. Descriptive statistics, non-parametric tests, and log-binomial regressions were used to address the research objectives. Results: This study found that the most prominent barriers to childhood vaccination were concerns regarding vaccine safety and side effects. Significant differences in vaccine barriers were observed across racial and ethnic groups for access barriers (p < 0.001), concern barriers (p = 0.006), and importance barriers (p < 0.001). Parents with lower education levels, children without health insurance, and lower-income families faced disproportionate challenges across two of the three barrier domains studied (access and perceived importance of vaccines). Additionally, concern barriers (aPR = 0.998, p < 0.001) and importance barriers (aPR = 0.997, p < 0.001) were strongly associated with the parent-reported prevalence of up-to-date vaccination status. Conclusions: Addressing parental vaccination barriers related to concern, access, and perceived importance is crucial, particularly for underserved populations including low-income families, uninsured parents, racial/ethnic minorities, and those with limited education. A sustained, equity-focused approach integrating scientific communication, community engagement, and policy interventions is essential for increasing vaccine uptake and ensuring equitable vaccination access.